Synthesis, Anti-Inﬂammatory, Analgesic, Molecular Modeling and Admet Studies of Novel Diclofenac Derivatives Containing Leucinyl Moiety - Elhenawy, A.A; El-Gazzar, M. A; Mohmoud, H. M; El-Eraky, W. I; El-Awdan, S.A. W (International Journal of Chemistry and Materials Research, 2013)
The present work aims to synthesize novel diclofenac derivatives containing L-leucine moiety. The synthesized compounds docked into the active site to discover validated inhibitors of cyclooxygenases (COX-1 and COX-2). The calculations in-silico were predicted that, the compound with lowest energy of docked poses was interacted with residues of active site, perhaps could be making them possible selective inhibitors against (COX-2) and physiologically active. The binding score of compound compared with reference drug, and show extensive interactions with the targets, which may consider it a suitable selective inhibitor against (COX-2).